Prevention of Online Gambling Crime as an Effort to Protect Children in Indonesia from the Perspective of Criminology - Islami, Michelia Zahra; Madjid, Abdul; Al-Uyun, Dhia (International Journal of Business, Law, and Education, 2024)
Throughout 2023, KiDi's pediatric clinic in Pejaten, South Jakarta treated nearly 50 children addicted to online gambling. From initially high school and junior high school teenagers, in the last three months it has been elementary school children in grades 5 and 6, mostly from upper middle class families. In the long run, their quality of life will deteriorate further. The impact of online gambling starts from no passion for life, not being able to focus on work, even getting into debt and the most fatal is to commit suicide. The focus of criminology is to find knowledge or reasons about social symptoms such as crime in society or why defendants commit their evil deeds. The purpose of this research is to find out and analyze regulations related to online gambling and child protection and analyze the causes of children committing online gambling in order to find out what prevention strategies are appropriate to minimize online gambling by children. Regulations related to online gambling are regulated as in Articles 303, 303 bis of the Criminal Code, Articles 426-427 of the new Criminal Code, and Article 27 paragraph (2) of the ITE Law. Meanwhile, child protection regulations are regulated in Law No. 35 of 2014 concerning Child Protection. Prevention efforts can be carried out by supervising the association of children and providing an understanding that online gambling is a bad act and can be charged with criminal sanctions.